Sexual Dimorphism for the Association between Vitamin D and Insulin Resistance in Chinese People. (6th March 2018) - Han, Bing; Li, Qin; Wang, Ningjian; Chen, Yi; Zhu, Chunfang; Chen, Yingchao; Xia, Fangzhen; Cang, Zhen; Lu, Meng; Meng, Ying; Chen, Chi; Lu, Yingli
Abstract : Background . The relationship between vitamin D and insulin resistance is still controversial. Many factors could influence this relationship. In addition, this relationship in different genders was still unclear. Methods . A total of 6597 subjects, including 2813 males and 3784 females, were analyzed. The serum levels of 25(OH)D, fasting blood glucose (FBG), fasting insulin, HbA1c, and other metabolic parameters were tested. The waist circumference (WC), weight, and height were also measured. Questionnaires regarding smoking and drinking were collected from these subjects. Results . Serum 25(OH)D was categorized into quartiles. Increasing 25(OH)D levels were associated with reduced trend of homeostasis model assessment of insulin resistance (HOMA-IR) in both males and females. Pearson's correlation indicated 25(OH)D level was inversely associated with the HOMA-IR for male subjects (r = − 0.055, P = 0.028 ) but not for female subjects (r = − 0.005, P = 0.798 ). Age, triglyceride (TG), and low-density lipoprotein (LDL) were associated with the vitamin D levels in males and females. In regression analysis, serum 25(OH)D concentration was significantly associated with HOMA-IR only in overweight males. Conclusion . We found an inverse association between 25(OH)D and HOMA-IR in Chinese overweight males. Vitamin D supplementation might be beneficial in this population. However, further clinical trials are needed to confirm this association.